Pt/IrO x enables selective electrochemical C-H chlorination at high current - Bo Wu; Ruihu Lu; Chao Wu; Tenghui Yuan; Bin Liu; Xi Wang; Chenyi Fang; Ziyu Mi; Surani Bin Dolmanan; Weng Weei Tjiu; Mingsheng Zhang; Bingqing Wang; et al. (Nature Communications)
Abstract Employing electrochemistry for the selective functionalization of liquid alkanes allows for sustainable and efficient production of high-value chemicals. However, the large potentials required for C(sp 3)-H bond functionalization and low water solubility of such alkanes make it challenging. Here we discover that a Pt/IrO x electrocatalyst with optimized Cl binding energy enables selective generation of Cl free radicals for C-H chlorination of alkanes. For instance, we achieve monochlorination of cyclohexane with a current up to 5 A, Faradaic efficiency (FE) up to 95% and stable performance over 100 h in aqueous KCl electrolyte. We further demonstrate that our system can directly utilize concentrated seawater derived from a solar evaporation reverse osmosis process, achieving a FE of 93.8% towards chlorocyclohexane at a current of 1 A. By coupling to a photovoltaic module, we showcase solar-driven production of chlorocyclohexane using concentrated seawater in a membrane electrode assembly cell without any external bias. Our findings constitute a sustainable pathway towards renewable energy driven chemicals manufacture using abundant feedstock at industrially relevant rates.